A living withness of the history: A cardiac shrapnel fragment - (:unkn) unknown (My University, 2005)
A 76-year-old Turkish Korean veteran suspected of having coronary artery disease, underwent coronary angiography. A foreign body was incidentally detected within the heart. The patient had joined the Korean War 55 years ago and had been injured by an explosive blast. The foreign body was one of the shrapnel fragments which had remained asymptomatic within the heart for 55 years.
Keywords: Cardiac sharapnel fragment; Foreing body; Korean war